Utilizing HSAF SE-E-SEVIRI (H10) Product to Track Seasonal and Monthly Variability in Snow Cover in Part of Southern Balkans - Alexandros Paraskevas; Vasileios Skarmintzos; Theodoros Stamatopoulos; Antonios Polyzos; Ioannis Matsangouras; Konstantinos Kasapas; Panagiotis Nastos (Environmental Sciences Proceedings, 2023)
Understanding the extent and location of snow cover is crucial for studying climate, hydrology, and ecosystems. Remote sensing, such as EUMETSAT’s H-SAF project, enables snow-cover monitoring using SEVIRI satellite data. This study analyzes the spatial variability of snow cover in the southern Balkans over the past five years, focusing on the H10 product. Results reveal distinct seasonal dynamics, with limited snow cover during autumn and extensive cover during winter. January and February exhibit the highest snowfall probability and better snow cover persistence compared to autumn. Winter exhibits greater extent, duration, and quality of snow cover (>80% in December and January, ~70% in February). These findings contribute to regional climate understanding and water resource management.